Bendahara yang Cerdik:: Cara Baru Memahami Luk 16:1b-8a dengan Analisis Naratif - Raden Paulus Edi Widiasta (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
Traditionally, the story about the manager in Luke 16:1b-8a is considered a difficult text. Apart from the controversial ending of the text, the details of the story are not easy to understand. Saint Cyril of Alexandria, in his commentary, said that trying to explain the details of the story is useless. The details of the story are taken only to form an allusion to the problem to be conveyed. The effect of neglecting this detail, for centuries, the act of reducing debts carried out by the manager was considered a dishonest act. By using narrative analysis, this article wants to show that reducing debt is not a dishonest act but a prudent act. It is precisely in the act of reducing the debt that the manager's prudence lies in the story.